2010
DOI: 10.2478/s11756-010-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Diel vertical migration and feeding of chaetognaths in coastal waters of the eastern Mediterranean

Abstract: This study investigates the diel vertical distribution and the diet of the most important chaetognath species found in the 0-50 m surface layer of a coastal area in the eastern Mediterranean during a 24-hour period in July 2004. Among the recorded chaetognaths, Sagitta enflata was the most abundant species (41.6%), followed by S. minima (32.5%) and S. serratodentata (20.8%). Those three species exhibited a "twilight migration" pattern, with only small differences among them. Vertical separation was found betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Mobile prey that, through a distinctive signal, elicit the sensory hairs are attacked: the chaetognath makes a bout with a rapid flick of the tail, the prey is blocked with the grasping spines and swallowed (Feigenbaum 1991). Adult copepods and copepodites are the main food resource of adult chaetognaths (Øresland 1987), while younger developmental stages may prefer copepod nauplii (Feigenbaum 1991); on occasion, cladocerans can become the mainstay of chaetognaths (Kehayias and Ntakou 2008;Kehayias and Kourouvakalis 2010). Feigenbaum (1977) hypothesised that the movement pattern and the swimming speed of the prey might affect its predation risk.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile prey that, through a distinctive signal, elicit the sensory hairs are attacked: the chaetognath makes a bout with a rapid flick of the tail, the prey is blocked with the grasping spines and swallowed (Feigenbaum 1991). Adult copepods and copepodites are the main food resource of adult chaetognaths (Øresland 1987), while younger developmental stages may prefer copepod nauplii (Feigenbaum 1991); on occasion, cladocerans can become the mainstay of chaetognaths (Kehayias and Ntakou 2008;Kehayias and Kourouvakalis 2010). Feigenbaum (1977) hypothesised that the movement pattern and the swimming speed of the prey might affect its predation risk.…”
Section: Introductionmentioning
confidence: 99%
“…Chaetognath species observed in the study area were evenly distributed in the Mediterranean Sea (Kehayias et al 1994(Kehayias et al , 1996Batistic et al, 2003;Duro and Saiz, 2000;Kehayias, 2003Kehayias, , 2004Kehayias et al, 2005;Kehayias and Ntakou, 2008;Kehayias and Kourouvakalis, 2010) and also in the İskenderun Bay (Terbıyık and Sarıhan, 2008;İşmen et al, 2003;Hazar, 2006;Terbıyık Kurt and Polat, 2013). (Terbıyık et al, 2007;Terbıyık and Sarıhan, 2008;Terbıyık Kurt and Polat, 2013).…”
Section: Discussionmentioning
confidence: 82%
“…(Terbıyık et al, 2007;Terbıyık and Sarıhan, 2008;Terbıyık Kurt and Polat, 2013). There are few studies on chaetognath feeding behaviour in the Mediterranean Sea and most of these studies reported data from the Aegean Sea (Kehayias et al, 2005;Kehayias and Kourouvakalis, 2010), Adriatic Sea (Batistic et al, 2003) and Western Mediterranean Sea (Duro and Saiz, 2000). The feeding ratios (FCR, NPC) determined in the present study are in agreement with the data reported from other regions of the Mediterranean Sea (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors already discussed that plankton nets with 200 µm mesh size could have under-sampled the smaller Chaetognatha species such as S. minima [33]. It is well known that the mesh size in plankton nets is a trade-off between the gain in larger species and loss of the smaller ones [34]–[35]. Despite these difficulties, we can present extensive and important data about the vertical and horizontal distribution of the Chaetognatha species with an emphasis on the ontogenetic development as well as being able to determine the trophic position of selected Chaetognatha species in the Benguela Upwelling System (BUS).…”
Section: Discussionmentioning
confidence: 99%